Dynamic neural network modulation associated with rumination in major depressive disorder: a prospective observational comparative analysis of cognitive behavioral therapy and pharmacotherapy - Nariko Katayama; Kazushi Shinagawa; Jinichi Hirano; Yuki Kobayashi; Atsuo Nakagawa; Satoshi Umeda; Kei Kamiya; Miyuki Tajima; Mizuki Amano; Waka Nogami; Sakae Ihara; Sachiko Noda; et al. (Translational Psychiatry)
Abstract Cognitive behavioral therapy (CBT) and pharmacotherapy are primary treatments for major depressive disorder (MDD). However, their differential effects on the neural networks associated with rumination, or repetitive negative thinking, remain poorly understood. This study included 135 participants, whose rumination severity was measured using the rumination response scale (RRS) and whose resting brain activity was measured using functional magnetic resonance imaging (fMRI) at baseline and after 16 weeks. MDD patients received either standard CBT based on Beck’s manual (n = 28) or pharmacotherapy (n = 32). Using a hidden Markov model, we observed that MDD patients exhibited increased activity in the default mode network (DMN) and decreased occupancies in the sensorimotor and central executive networks (CEN). The DMN occurrence rate correlated positively with rumination severity. CBT, while not specifically designed to target rumination, reduced DMN occurrence rate and facilitated transitions toward a CEN-dominant brain state as part of broader therapeutic effects. Pharmacotherapy shifted DMN activity to the posterior region of the brain. These findings suggest that CBT and pharmacotherapy modulate brain network dynamics related to rumination through distinct therapeutic pathways.